Student Perceptions of Digital Literacy in Fiqh Education at Sunan Ampel State Islamic University of Surabaya - Saiful Jazil; Ahmad Zahro; Muh. Sholihuddin; Syamsun Ni'am; Anin Nurhayati (UIN Sunan Ampel Surabaya, 2022)
In the era of industry 4.0, it is so easy for students to take digital information instantly without any activity to ensure the validity of previous information. This study aims to analyze students' perceptions of digital literacy skills in fiqh learning at State Islamic University (UIN) Sunan Ampel Surabaya. This research is qualitative with phenomenological glasses. The informants in this study were 160 students. Brande filled out an online questionnaire through a google form containing statements related to the basic digital literacy skills that have been developed. Then we conducted a semi-structured interview on the informant's answer results directly. The results of the study revealed that students have a good perception of literacy skills. They are ready to use tools to search, dig, select and process information. However, students have not mastered the basic tools for learning fiqh, namely Arabic. Students experience problems when looking for fiqh information in Arabic. The recommendation in this study is that students will not be optimal in fiqh learning if they only have digital literacy skill but the fiqh learning base is not yet qualified. They need a fiqh website that is in Indonesian with credible and valid references.